Effects of a stepwise alveolar recruitment maneuver on lung volume distribution in dogs assessed by computed tomography - Sanchez, Ana Flávia; Ambrósio, Aline Magalhães; Pinto, Ana Carolina B. C. Fonseca; Pereira, Marco Aurélio Amador; Andrade, Felipe Silveira Rego Monteiro; Rodrigues, Renata Ramos; de Carvalho Martins, Alessandro Rodrigues; Baroni, Carina Outi; Ferrante, Bruno; Fantoni, Denise Tabacchi (Frontiers in Veterinary Science, 2024)
Background: Pulmonary atelectasis is a common event that occurs during anesthesia. In these cases, mechanical ventilation (MV) associated with alveolar recruitment maneuvers (ARM) and positive endexpiratory pressure (PEEP) is indicated to reverse the condition, ensuring adequate gas exchange and improving oxygenation. ARM can trigger volutrauma, barotrauma, and atelectrauma. Therefore, computed tomography (CT) represents the gold-standard method for monitoring lung aeration after ARM. Objective: Evaluate lung volume distribution after stepwise ARM assessed by CT. Methods: Were evaluated 12 dogs weighing 24.0 ± 6.0 kg, aged 3 ± 1 years old, of both sexes and different breeds, submitted to orchiectomy or ovariohysterectomy. The animals were anesthetized and ventilated in volume-controlled mode. Then, ARM was started by PEEP titration (5, 10, 15, 20 cmH2O). CT scans, cardiovascular parameters, and ventilatory mechanics were evaluated at all time points. Data were assessed for normality with the Shapiro-Wilk test and two-way ANOVA followed by a post hoc Bonferroni test to identify differences between time points. Statistical significance was attributed when p < 0.05. Results: CT demonstrated that ARM increased ventilation throughout the lung, including the dependent regions, with volumes that increased and decreased proportionally to PEEP titration. When they reached PEEP 10 and 5 cmH2O descending (d), they remained significantly higher than in PEEP 0 cmH2O (baseline). There was an improvement about 40% in static compliance (Cst) at PEEP 10d and PEEP 5d compared to baseline. There was an increase in heart rate (HR) from PEEP 15 increasing (i) (74.5%) to PEEP 10d (54.8%) compared to baseline. Mean arterial blood pressure (MABP) decreased about 9% from PEEP 15i to PEEP 15d compared to baseline.The lung attenuation, regional, and global volumes assessed by CT show that maximum pulmonary aeration distribution followed PEEP titration occurred at PEEP 20 cmH2O, maintaining the lungs normoaerated and without hyperaeration.